KONTEKSTUALISASI HADIS “KECANTIKAN SEBAGAI SALAH SATU KRITERIA PEREMPUAN IDAMAN” TERHADAP KAUM DIFABEL: Analisis Hermeneutika Double Movement Fazlur Rahman - Muhammad Alfreda Daib Insan Labib; Khulanah Khulanah; Muhammad Ghossan Nazhif Dhiya’elhaq; Hanan Aslamiyah Thoriq (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2025)
This article discusses the analysis of hadiths related to the criteria for women in Islam who are recommended to marry. Of the four criteria mentioned (beauty, wealth, lineage, and religion), the researcher specified the study to one of the four, namely beauty. This is the background to the widespread use of this hadith as defence against refusing to marry women who are not beautiful, especially those with disabilities. Misunderstanding of this hadith has implications for discrimination against people with disabilities. This research method is descriptive analysis, namely describing the data that has been collected and then analyzing the data. Some of the focuses of discussion in this article include; 1). What is the quality of the hadith on the four criteria for a dream woman in Islam? 2). What is the meaning of this hadith if analyzed using hermeneutics double movement Fazlur Rahman? 3). How to address societal heterogeneity in the interpretation of this hadith? One of the conclusions from this article is that the meaning of hadith like this actually tends to create division rather than problem solving, so it is necessary to provide proper socialization and interpretation of the hadith on the four criteria for the ideal woman.Tulisan ini membahas tentang analisis hadis terkait krtieria perempuan dalam Islam yang dianjurkan untuk dinikahi. Dari empat kriteria yang disebutkan (kecantikan, harta, nasab, dan agama), peneliti menspesifikasikan kajian kepada salah satu di antara empat, yaitu kecantikan. Hal ini di latar belakangi maraknya penggunaan hadis ini sebagai defence terhadap penolakan menikahi perempuan yang tidak cantik terlebih difabel. Salahnya pemahaman hadis tersebut berimplikasi pada diskriminasi terhadap kaum difabel. Metode penelitian ini adalah deskritif analisis, yaitu melakukan deskripsi terhadap data yang telah dihimpun kemudian melakukan analisis terhadap data tersebut. Beberapa fokus pembahasan dalam tulisan ini di antaranya adalah; 1). Bagaimana kualitas hadis empat kriteria perempuan idaman dalam Islam? 2). Bagaimana makna hadis tersebut jika dianalisis menggunakan hermeneutika double movement Fazlur Rahman? 3). Bagaimana menyikapi hegerogenitas masyarakat dalam interpretasi hadis tersebut? Di antara kesimpulan dari tulisan ini salah satunya adalah pemaknaan hadis yang seperti itu justru cenderung menghadirkan perpecahan daripada problem solving, sehingga perlu diberikan sosialisasi dan interpretasi yang tepat terhadap hadis empat kriteria wanita idaman.